MODERN TECHNOLOGIES AND TOOLS FOR DEVELOPING WEB SITES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses a brief literature review of the mechanisms and tools for developing websites; modern technologies, stages, tools, and means of developing websites are considered; the main approaches and methods of development are given; current trends are analyzed and summarized, and the most promising tools in the web industry are described. Currently, there is a need for modern mobile and interactive web applications that not only provide users with information but also allow them to perform certain functions: receive or order goods and services, provide access to a personal account where customers can manage their accounts, loans. Even small businesses must provide online tools for their customers to successfully market their business in today’s world. In order to successfully run your business, you need a well-designed website that would work correctly on all devices, regardless of the operating system used. In this article, we will try to analyze what web technologies exist in web design.
Keywords: website development, web design tools, web development approaches and methods, SaaS services, and PaaS platforms, development trends in the web industry.